Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 5 - Section 5.1 - Fundamental Operations - Exercise - Page 214: 41



Work Step by Step

We are given: $x=-1$, $y=2$, $z=-3$ We take into account the order of operations: Parenthesis, Exponents, Multiplication/Division, Addition/Subtraction Thus, we have: $$\frac{x^2+(z-y)^2}{4x^2+z^2}=\frac{(-1)^2+(-3-2)^2}{4(-1)^2+(-3)^2}\\ =\frac{1+(-5)^2}{4+9}=\frac{1+25}{13}=\frac{26}{13}=2 .$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.